Zjawisko firm zombie i jego przyczyny - Góra, Daniel (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The aim of this paper is to specify and describe the factors that contribute to the prevalence of zombie firms, defined as old, unprofitable, nearly insolvent firms which normally would exit the market. Based on the review of the literature, mostly published by the Organization for Economic Co-operation and Development (OECD), the Bank for International Settlements (BIS) and central banks, we conclude that the main causes of the rise of zombie firms in the last 10–20 years have been loose monetary policy (especially after the outbreak of the financial crisis of 2007–2008), weak banking sector, overbanking of economies, government subsidies to enterprises and weaknesses of insolvency law. We consider the zombification of economies as a highly important issue since zombie companies could be lowering the pace of capital formation, productivity and economic growth by raising entry barriers, curbing Schumpeterian creative destruction and misallocating capital.
Keywords: zombie firms; bankruptcies; monetary policy; bank forbearance; capital misallocation